Integrasi Rapor Kurikulum Merdeka pada Sistem Informasi Akademik Sekolah Sukma Bangsa Bireuen - Fikhri, Aditya Aziz (Yayasan Sukma Bangsa, 2024)
The Merdeka Curriculum is a curriculum with a learning design that provides opportunities for students to learn calmly, comfortably, pleasantly and stress-free as well as expressing their natural talents (Rahayu et al. 2022). The independent curriculum is also an educational innovation that aims to provide more freedom for teachers and schools in developing learning materials that are relevant to the local context and student needs. With this approach, students are expected to be able to learn more independently, creatively, and according to their interests and talents. One important aspect in implementing the Independent Curriculum is how it is integrated into the system for assessing and reporting learning outcomes, such as student report cards. This integration aims to ensure that evaluation of students not only covers academic aspects, but also the development of their holistic character, skills and competencies. This journal article discusses how the integration of Independent Curriculum report cards can be implemented in the Sukma Bangsa Bireuen School Academic Information System. The academic information system that is integrated with the Merdeka Curriculum is expected to support more efficient, transparent and accurate management of assessment data. The results of the integration have been implemented in class X at Sukma Bangsa Bireuen School. With the existence of an academic information system that is integrated with the Independent Curriculum, it is hoped that a more effective learning environment can be created and supports optimal holistic development of students.